EXTH-54. ENHANCED SENSITIVITY OF HUMAN GLIOMA CELLS FOR TEMOZOLOMIDE (TMZ) BY COMBINING THERAPY WITH HEAT SHOCK PROTEIN 90. (9th November 2020) - Sharma, Pratibha; Mahadevan, Lakshmi Shree K; Argall, Aaron; Xu, Jihong; Sampath, Deepa; Puduvalli, Vinay
Abstract: BACKGROUND: Heat-shock protein 90 (HSP90) is a molecular chaperone involved in the conformational maturation of many client proteins that regulate cell proliferation, survival, and apoptosis. Due to the limited solubility of natural Hsp90 inhibitors, synthetic inhibitors with a more potent impact are being developed. In this study we examined the biological activity of a potent synthetic small molecule Hsp90 inhibitor, SNX‐5422 (PF‐04929113)and assessed its ability of to inhibit the growth of glioma and to synergize with temozolomide. We also examined the ability of SNX-5422 to cross the blood brain barrier (BBB) and to achieve target inhibition in vivo . METHODS: Using a combination of in vitro techniques, the effect of SNX-5422 on the biological impact and HSP90 client protein signaling were studied in glioma lines and patient-derived glioma stem like cells. Its efficacy as a single agent or in combination with TMZ was also assessed in vitro . To assess SNX-5422 ability to cross blood brain barrier, brain and plasma pharmacokinetics was performed in non-tumor bearing mice. RESULTS: SNX‐5422 exhibited potent growth inhibition in both glioma cells and GSCs with an IC50 range of 100‐500nM, and inhibited pro‐survival signal kinases, phospho‐Akt, p-ERK1/2 and p-S6 following treatment in GSC262 and GSC811. This was accompanied by accumulation of apoptotic cells following SNX‐5422 exposure. Combination studies with TMZ showed a synergestic impact on glioma cell proliferation. Pharmacokinetics studies showed a significant drug penetrance into the intact brain further supported by elevated levels of HSP70 (molecular maker for HSP90 inhibition) by IHC. CONCLUSIONS: SNX‐5422 is effective in downregulating Hsp90 client proteins required for glioma cell survival. In addition, SNX‐5422 inhibits tumor growth by promoting apoptosis through modulation of several key signaling pathways and sensitizes glioma cells to TMZ. Given also that SNX‐5422 crosses BBB, it warrants further investigation as a clinical agent for treatment of gliomas.